Methanolysis of Jatropha oil in the presence of potassium hydroxide as catalyst - Syam Mohan, Murali Mohan; Yunus, Robiah; Mohd Ghazi, Tinia Idaty; Choong, Thomas Shean Yaw (Asian Network for Scientific Information, 2009)
An improved method in biodiesel production using jatropha curcas oil is discussed in this study. There are two steps process involved namely esterification and transesterification. The first step serves as a pre-treatment process to reduce the free fatty acid content in the feedstock and the second step converts the oil into biodiesel. The reaction time, molar ratio, reaction temperature and percentage of catalyst loading are the operating parameters being optimized in the study. After the pre-treatment step, the free fatty acid content of Jatropha oil has been reduced to less than 1%. The treated oil was transesterified using potassium hydroxide catalyst. The optimum conditions are 65°C, molar ratio of methanol to oil at 6:1, percentage of catalyst loading at 1% and reaction time of 60 min.